Strategy for Developing Kerawang Gayo Crafts in Central Aceh Regency - Ernawati, Ernawati; Muharramsyah, Rambang; Novalita, Rahmi (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research describes the strategy for developing Kerawang Gayo crafts as a tourist attraction. This research method uses a qualitative approach. The research location is Bebesan District, Central Aceh Regency. The research informants were key informants, namely kerawang Gayo craftsmen. This research also uses the principles of documentation, inventory and tourism approaches. Data analysis uses data reduction, data display, and data reduction. The results of the research show that the strategy for developing Kerawang Gayo crafts can be carried out through: a) preserving the culture of kerawang Gayo crafts, b) utilizing Gayo kerawang crafts as a tourist attraction product, c) increasing public awareness of tourism, d) developing filigree craft centers Gayo as a tourist destination, e) developing the quality of craftsmen in the Gayo kerawang craft center, f) developing special interest tourism packages, g) collaborating with the government in providing tourism supporting infrastructure, and g) carrying out promotions through collaboration with various parties in including travel agencies, as well as h) tourism service providers